Social Status Controls Somatostatin Neuron Size and Growth - Hofmann, Hans A. (J Neurosci, 2000)
Many animal species show flexible behavioral responses to environmental and social changes. Such responses typically require changes in the neural substrate responsible for particular behavioral states. We have shown previously in the African cichlid fish,Haplochromis burtoni, that changes in social status, including events such as losing or winning a territorial encounter, result in changes in somatic growth rate. Here we demonstrate for the first time that changes in social status cause changes in the size of neurons involved in the control of growth. Specifically, somatostatin-containing neurons in the hypothalamus of H. burtoni increase up to threefold in volume in dominant and socially descending animals compared with cell sizes in subordinate and socially ascending fish. Because somatostatin is known to be an inhibitor of growth hormone release, the differences in cell size suggest a possible mechanism to account for the more rapid growth rates of subordinate and socially ascending animals compared with those of dominant or socially descending fish. These results reveal possible mechanisms responsible for socially induced physiological plasticity that allow animals to shift resources from reproduction to growth or vice versa depending on the social context.